KERAGAAN PETANI KELAPA SAWIT POLA KKPA DALAM MENGHADAPI SERTIFIKASI DI DESA BINA BARU KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR - Stifany Christin; Sakti Hutabarat; Novia Dewi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Increasing demand for oil palm fruit and higher price of fresh fruit bunches have motivated huge investors and farmers to increase their oil palm production. Since land expansion was considered to be cheaper and easier to implement than intensification, new planting become more populer in order to increase oil palm production. However, there are many negative impacts following the expansion of oil palm plantation, such as deforestation, biodiversity loss, land degradation, GHG emission, and land conflicts. A number of private and non-governmental institutions have created certification system to halt the destruction of the forest and environtment. All oil palm products must comply to the standard to be included in the supply chain. This situation becomes a dilemma for oil palm smallholders. The conversion from convensional to sustainable oil palm production needs a huge of costs while smallholders have less access to various aspect related to oil palm production including access to finance. The objective of this study is to analyse the existing performance of oil palm smallholders including good agricultural practices, best management practices, farm income, and household income. This study use a survey method to collect primary data on 83 sample in the village. The result shows that the majority of the smallholders do not apply best practices in their plantation. Consequently, the quantity and quality of their oil palm fuits are considerably low. A lot of work have to be done if the smallholders would like to obtain certification. Keywords :good agricultural practices, farmincome, household income, certification